DIGITAL LITERACY OF BIOLOGY TEACHERS AND ITS IMPACT ON LEARNING INNOVATION IN BANDA ACEH SCHOOLS - Rosma, Fatemah; Suwarniati, Suwarniati; Hasanah, Mauizah; Manja, Manja (Jurnal Biologi Sains dan Kependidikan, 2025)
Given the current state of digital technology, educators must be proficient in digital literacy in order to facilitate creative and efficient teaching methods. The purpose of this study is to characterize biology teachers' levels of digital literacy and examine how they relate to innovative teaching practices in Banda Aceh secondary schools. The study included biology teachers from a number of secondary schools that were specifically chosen, and it used a qualitative approach and case study methodology. In-depth interviews, observations, and documentation were used to gather data. According to the findings, the majority of teachers had a moderate degree of digital literacy. While the use of interactive digital learning platforms remained relatively low, technology use was still restricted to online communication and the creation of presentation media. Teachers faced a number of challenges, such as inadequate governmental support, a lack of ongoing training, and limited facilities. All things considered, it can be said that biology instructors' degree of digital literacy has a big impact on the variety and caliber of instructional innovation used in the classroom. As a result, it is advised that educational officials and schools strengthen their support by integrating ICT into curriculum plans, offering technological infrastructure, and providing training in digital literacy. It is anticipated that these initiatives will encourage more imaginative, participatory, and contextual learning.